Validation of the Wisconsin upper respiratory symptom survey-24, Chinese version. (31st December 2022) - Wang, Yuanyuan; He, Zehui; Chen, Simin; Liu, Yuntao; Li, Fang; Barrett, Bruce; Zhang, Zhongde; Su, Guobin; Stålsby Lundborg, Cecilia
Abstract: Background: The Wisconsin upper respiratory symptom survey (WURSS) is a validated English questionnaire to evaluate the quality of life and severity of upper respiratory tract infections (URTIs). We aimed to develop a Mandarin Chinese version of WURSS-24 (WURSS-24-C) and evaluate its reliability, validity and minimal important difference (MID). Methods: The WURSS-24-C was developed using the forward-backward translation procedure. People with URTIs' symptoms within 48 h of onset were recruited and asked to fill in the WURSS-24-C daily for up to 14 d. Exploratory and confirmatory factor analyses were used to suggest domains. The 8-Item Short Form Health Survey (SF-8) assessing general mental and physical health was used to assess validity. Reliability estimated by Cronbach's alpha and mean day-to-day change for those indicating minimal improvement as MID were evaluated. Results: The WURSS-24-C was found to be acceptable, relevant, and easy to complete in cognitive debriefing interviews. A total number of 300 participants (age 28.4 ± 9.3, female 70%) were monitored for 2500 person-days. Four domains (activity and function, systemic symptoms, nasal symptoms and throat symptoms) of the WURSS-24-C were confirmed (comparative fit index [CFI] = 0.93). The reliability of this 4-domain-structure is good (Cronbach's alphas varied from 0.849 to 0.943). Convergent validity is moderate (Pearson correlation coefficients between daily WURSS-24-C and the SF-8 were −0.780 and −0.721, for the SF-8 physical and mental health, respectively). Estimates of MID for individual items varied from −0.41 to −1.14. Conclusions: The WURSS-24-C is a reliable and valid questionnaire for assessing illness-specific quality-of-life health status in Chinese-speaking patients with URTIs. Key messages: The Wisconsin upper respiratory symptom survey (WURSS) series are patient-oriented questionnaire instruments assessing the quality of life and severity of upper respiratory tract infections (URTIs). The WURSS-24 was translated into Mandarin Chinese using the forward-backward translation procedure, and evaluated its validity, reliability and minimal important difference (MID) in 300 Chinese participants with URTIs. The WURSS-24 Chinese version (WURSS-24-C) seems to be a reliable and valid questionnaire for assessing illness-specific quality-of-life health status in Chinese patients with URTIs.